The 'Wetiko' legal principles: Cree and Anishinabek responses to violence and victimization - Friedland, Hadley Louise (University of Toronto Press, 2018)
"In Algonquian folklore, the wetiko is a cannibal monster or spirit that possesses a person, rendering them monstrous. In The Wetiko Legal Principles, Hadley Friedland explores how the concept of a wetiko can be used to address the unspeakable happenings that endanger the lives of many Indigenous children. Friedland critically analyses Cree and Anishinabek stories and oral histories alongside current academic and legal literature to find solutions to the frightening rates of intimate violence and child victimization in Indigenous communities. She applies common-law legal analysis to these Indigenous stories and creates a framework for analysing stories in terms of the legal principles that they contain. The author reveals similarities in thinking and theorizing around the dynamics of wetikos and offenders in cases of child sexual victimization. Friedland's respectful, strength-based, trauma-informed approach builds on the work of John Borrows and is the first to argue for a legal category derived from Indigenous legal traditions. The Wetiko Legal Principles provides much needed direction for effectively applying Indigenous legal principles to contemporary social issues."--Provided by publisher